Iron Overload Cardiomyopathy - Retno Eka Sari; Wahyudi (Sumatera Medical Journal, 2024)
Background: Iron overload cardiomyopathy is a condition of excessive iron accumulation in cardiomyocytes due to abnormal iron absorption or repeated blood transfusion. Objective: This literature review was to discuss about iron overload caediomyopathy. Methods: This was a literature revew that explored about iron overload caediomyopathy based on other research. Results: In the early stages, the patient may be asymptomatic with good ventricular systolic function. Iron deposit in ventricular cause dyspnea on effort due to left ventricular systolic dysfunction then in atrial cause atrioventricular block and supraventricular arrhythmic. For severe symptom due to dilated cardiomyopathy is characterized by left ventricular dilatation and risk of sudden cardiac death. Diagnosis of iron overload cardiomyopathy can be made if there is evidence of heart disease, the presence of iron overload (serum ferritin > 300 ng/mL and transferrin saturation > 55%) and cardiac siderosis with cardiac MRI T2 * < 20 ms as gold standard. Patient management involves lowering systemic iron levels and preventing iron entry into cardiomyocytes. Therapy with phlebotomy or iron chelation as indicated. Conclusion: Administration of calcium channel blockers and resveratrol antioxidant therapy may be considered to reduce morbidity and mortality due to cardiac siderosis.